Perspective Paper – Sustainability Assessment of Organic Farming Practices: A Comparison of Key Tools - Aashiq Hussain Lone (Colombo Business Journal, 2022)
Sustainable agricultural production is essential for an adequate food supply to feed the global population. One facet of efforts in making the agricultural sector more sustainable is the dramatic increase in organic farming (OF). With its current popularity, people across the globe are increasingly interested in the sustainable performance of organic production. However, accurate and timely information is scarce and there is a lacuna of knowledge among organic farmers about Sustainability Assessment (SA). Many promising SA measurement tools have been developed for the organic farming sector. However, improved procedures and a broader common knowledge are still necessary. In response, this paper provides a comprehensive comparison and scientific underpinning of the prominent tools for assessing farm sustainability to provide support for monitoring sustainable development in OF practices. This comparison can contribute to the adoption of suitable SA tools, and, thereby, the achievement of the United Nations (UN) Sustainable Development goals by 2030.